NO LINKS!!
Write an equation to represent the following graphs:
a. passes through (-2, 18.75 and (1, 1, 1.2)
a-value:___________ b-value:____________
Equation: _____________________

b. passes through (0, 6) and (2, 8.64)
a-value:_____________ b-value:_____________
Equation:________________________

Respuesta :

Answer:

[tex]\textsf{a)\;\;passes\;through\;$(-2, 18.75)$\;and\;$(1, 1.2)$}[/tex]

     [tex]\textsf{$a$-value:\;\;3 \quad $b$-value: \;\;0.4}[/tex]

     [tex]\textsf{Equation: \quad $y=3 (0.4)^x$}[/tex]

[tex]\textsf{b)\;\;passes\;through\;$(0, 6)$\;and\;$(2, 8.64)$}[/tex]

     [tex]\textsf{$a$-value:\;\;6 \quad $b$-value: \;\;1.2}[/tex]

     [tex]\textsf{Equation: \quad $y=6 (1.2)^x$}[/tex]

Step-by-step explanation:

[tex]\boxed{\begin{minipage}{9 cm}\underline{General form of an Exponential Function}\\\\$y=ab^x$\\\\where:\\\phantom{ww}$\bullet$ $a$ is the initial value ($y$-intercept). \\ \phantom{ww}$\bullet$ $b$ is the base (growth/decay factor) in decimal form.\\\end{minipage}}[/tex]

Part (a)

Given points:

  • (-2, 18.75)
  • (1, 1.2)

Substitute both points into the exponential function formula to create two equations:

  • [tex]\textsf{Equation\;1}: \quad 18.75=ab^{-2}[/tex]
  • [tex]\textsf{Equation\;2}: \quad 1.2=ab[/tex]

Divide the equations to eliminate a, then solve for b:

[tex]\implies \dfrac{18.75}{1.2}=\dfrac{ab^{-2}}{ab}[/tex]

[tex]\implies15.625=\dfrac{b^{-2}}{b}[/tex]

[tex]\implies15.625=b^{-2}b^{-1}[/tex]

[tex]\implies15.625=b^{-3}[/tex]

[tex]\implies15.625=\dfrac{1}{b^{3}}[/tex]

[tex]\implies b^{3}=\dfrac{1}{15.625}[/tex]

[tex]\implies b=0.4[/tex]

Substitute the found value of b into the second equation and solve for b:

[tex]\implies 1.2=0.4a[/tex]

[tex]\implies a=3[/tex]

Therefore, the exponential equation is:

[tex]y=3 (0.4)^x[/tex]

-------------------------------------------------------------------------------------------

Part (b)

Given points:

  • (0, 6)
  • (2, 8.64)

Substitute point (0, 6) into the exponential function formula and solve for a:

[tex]\implies 6=ab^0[/tex]

[tex]\implies 6=a(1)[/tex]

[tex]\implies a=6[/tex]

Substitute the found value of a and point (2, 8.64) into the exponential function formula and solve for b:

[tex]\implies 8.64=6b^2[/tex]

[tex]\implies b^2=\dfrac{8.64}{6}[/tex]

[tex]\implies b^2=1.44[/tex]

[tex]\implies b=\sqrt{1.44}[/tex]

[tex]\implies b=1.2[/tex]

Therefore, the exponential equation is:

[tex]y=6 (1.2)^x[/tex]